Smooth Particle Hydrodynamics Study of Sediment Profile Erosion - Azman A.; Zawawi M.H.; Radzi M.R.M.; Abas A.; Aziz N.A. (Institute of Physics Publishing, 2023)
A sediment profile erosion with interaction of water which moving with wave generator are model in three-dimensional (3D) by using numerical method Smooth Particle Hydrodynamics (SPH). The code is constructed using SPH formulation from Monaghan and both sediment and water are modelled as weakly compressible viscous fluids. The wave generator is set with a constant sinewave of 0.24sin(2.6?t). The sediment model with slope angle 36.464 is constructed in Solidworks with boundary length of 1206 mm, width of 454 mm and height of 463 mm. Meanwhile, the model is simulated in period of 15s. A sensitivity analysis is performed in order to add degree of trustiness to the results. The impact of generated wave to the sediment profile is analysed. The result show that the sediment starts eroded at 3 s. Afterwards, the sediment continued eroded whereby the sediment starts to move from the top region to lower region. This phenomenon due to swash and backwash of the wave that being generated by wave generator. Thus, the results show that the sediment erosion successfully simulated by using SPH. Published under licence by IOP Publishing Ltd.